Employee engagement amid and post the Covid-19 pandemic in a South African debt collection organisation - Botha, Doret (Journal of Economic Development, Environment and People, 2025)
In the post-Covid-19 pandemic era, there is increasing interest in the implementation of flexible work arrangements such as remote work. Previous research revealed that remote work environments may affect the engagement levels of employees positively or negatively. This article reports on the results of three studies conducted amid and post the Covid-19 pandemic, measuring the engagement levels of employees in a debt collection organisation in South Africa. The research results suggest that remote work has the potential to enhance employee engagement levels. Consequently, management should consider maintaining or implementing flexible working arrangements, such as remote work, to foster and sustain employee engagement. Additionally, the findings suggested that factors such as gender, age and educational attainment may influence employee engagement levels. The findings highlight the importance of understanding employee engagement and its contributing factors across various work environments, including flexible work arrangements such as remote and hybrid work.